2010
DOI: 10.1093/europace/eup433
|View full text |Cite
|
Sign up to set email alerts
|

Chronotropic incompetence and autonomic dysfunction in patients without structural heart disease

Abstract: Our data suggested that CI in patients without structural heart disease was mainly caused by a pathophysiological condition in which sympathetic activation was not well translated into heart rate increase. Further study is needed to determine the post-synaptic sensitivity of the beta-adrenergic receptor pathway in relation to CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 37 publications
(32 reference statements)
1
24
0
Order By: Relevance
“…27 The most often used criteria to diagnose CI is a failure to reach an arbitrary percentage (usually 80%) of the age-predicted maximal HR or a failure to attain 80% of the HR reserve from rest to peak exercise (CRI). 16,24,27 We defined CI by a strict criteria requiring both these conditions to be met.…”
Section: Discussionmentioning
confidence: 99%
“…27 The most often used criteria to diagnose CI is a failure to reach an arbitrary percentage (usually 80%) of the age-predicted maximal HR or a failure to attain 80% of the HR reserve from rest to peak exercise (CRI). 16,24,27 We defined CI by a strict criteria requiring both these conditions to be met.…”
Section: Discussionmentioning
confidence: 99%
“…This ultimately results in post-synaptic desensitization [63][64][65][66]. As the HR response to exercise is determined by the extent of sympathetic drive to the heart and the ability of b-adrenergic receptors in the sinoatrial node to respond to circulating catecholamines, such desensitization could then result in a disturbed HR regulation/ response during exercise [64,67]. Thus, hyperglycaemia in T2DM patients induces CAN, leading to sympathetic predominance, ultimately contributing to development of CI by post-synaptic desensitization of the b-adrenergic receptor pathways in the sinoatrial node.…”
Section: Cardiovascular Autonomic Neuropathymentioning
confidence: 99%
“…Phan et al [8] found that 34% of patients with HFpEF have CI during maximal exercise when defined by %Max PHR and 63% when defined by %HRR. In order to avoid age, functional capacity and resting HR biases of each individual [1,4,5,[20][21][22][23][24], for comparison analysis of patient data we have used %HRR. It is now well known that both parameters of CI were associated with adverse risk profile, whereby %HRR represents an isolated measure of chronotropy that appeared as an independent predictor of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms linking smoking to CI remain unclear. There are a number of potential mechanisms including endothelial dysfunction, increased ischaemic burden, increased peripheral vascular resistance, autonomic dysfunction and/or downstream deficits in betaadrenergic stimulation [21,28,29], all mechanisms which are inevitably connected to HFpEF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation